P76 General and respiratory health outcomes in adult survivors of bronchopulmonary dysplasia: a systematic review. (16th November 2010) - Gough, A; Spence, D; Linden, M A; McGarvey, L; Halliday, H
Abstract : Introduction and objectives: Bronchopulmonary dysplasia (BPD) is the most common form of chronic lung disease in infancy and the second most common after asthma in children. With the improved survival of extremely preterm infants the incidence of BPD has increased. Currently there is only limited information on the health of BPD survivors who have reached adulthood. The purpose of this systematic literature review was to examine current empirical research on adult survivors of BPD. Methods: Six electronic databases were searched between 1950 and February 2010 (Medline, PubMed, Embase, PsycINFO, Cumulative Index of Nursing and Allied Health Literature (CINAHL Plus) and Web of Knowledge. Studies were independently screened and were only included if they related to the assessment of outcome measures in adult survivors of BPD. From a total of 1453 search results, 14 eligible studies were included in the review. Data on methodological design and findings were extracted from each included study; in addition the methodological quality of each study was assessed using the Critical Appraisal Skills Programme ( CASP ) checklist. Results: 14 cohort studies met the review criteria. 12 scored highly on the CASP checklist, with a score >10 out of 12. No study scored less than 7. Nine studies included a control group and only four studies in total had a singular focus on BPD outcomes. Six controlled studies found differences between the groups on respiratory symptoms. 11 studies carried out lung function testing and found evidence of airflow obstruction. Of these, one study found no difference between preterm and controls. However, there were only seven adults who were born preterm with BPD in this study. Five studies in total examined radiographical outcomes, and all found evidence of abnormalities. Those with moderate-severe BPD were found to be most affected compared to mild BPD subjects. Conclusions: The effects of BPD on pulmonary function do not diminish over time. This may reflect issues related to means of testing, differing definitions and classification of BPD, and the adaptation of individuals to their circumstances over time.